2021
DOI: 10.3389/fonc.2021.718876
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA FOXP4-AS1 Promotes Progression of Ewing Sarcoma and Is Associated With Immune Infiltrates

Abstract: Ewing sarcoma (ES) is a highly malignant primary bone tumor with poor prognosis. Studies have shown that abnormal expression of lncRNA influences the prognosis of tumor patients. Herein, we established that FOXP4-AS1 was up-regulated in ES and this correlated with poor prognosis. Further analysis illustrated that FOXP4-AS1 down-regulation repression growth, migration, along with invasion of ES. On the contrary, up-regulation of FOXP4-AS1 promoted the growth, migration, as well as invasion of ES. To explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Furthermore, lncRNA FOXP4-AS1 was downregulated in three thyroid carcinoma cell lines compared to normal thyroid cells ( Figure 1I ). Besides, the fluorescence in situ hybridization (FISH) results showed that FOXP4-AS1 distributes predominantly in the PTC cell cytoplasm ( Figure 1J ), which was consistent with Xiong et al.’s report ( 22 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, lncRNA FOXP4-AS1 was downregulated in three thyroid carcinoma cell lines compared to normal thyroid cells ( Figure 1I ). Besides, the fluorescence in situ hybridization (FISH) results showed that FOXP4-AS1 distributes predominantly in the PTC cell cytoplasm ( Figure 1J ), which was consistent with Xiong et al.’s report ( 22 ).…”
Section: Resultssupporting
confidence: 91%
“…It was researched that FOXP4-AS1 can not only modulate the epigenetic modification of the genome by recruiting epigenetic modification proteins in the nucleus but also affect the regulation of miRNAs on target genes by acting as a molecular sponge for miRNAs in the cytoplasm, in tumor studies. We went further to detect its subcellular localization and found that it localized at the cytoplasm of thyroid cells consistent with a previous report ( 22 ). Therefore, we speculate that FOXP4-AS1 functions as a tumor suppressor in PTC through two possible ways: acting as a miRNA sponge or regulating the stability of its binding proteins.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…lncRNAs are RNA molecules with transcripts that are longer than 200 nucleotides, which were initially thought to be by-products of RNA polymerase II transcription [4]. lncRNAs are important regulatory molecules in the process of tumorigenesis [5][6][7]. In addition, lncRNAs are also associated with tumor invasion, in ltration, metastasis, and prognosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the elimination and equilibrium phases, sarcoma-secreted exosomes containing lncRNA FOXP4-AS1 could recruit innate immune cells to TME, including Tregs, activated NK cells, and M1 macrophages [ 54 ]. The infiltrating immune cells had either tumor-promoting or tumor-suppressive effects.…”
Section: The Roles Of Exosomes In Sarcoma Tmementioning
confidence: 99%